Conceptualising teacher dialogic artistry: a nexus of pedagogical dispositions and language qualities - Hadjipanteli, Angela; Vrikki, Maria (Frontiers in Education, 2023)
Teacher pedagogical artistry is fundamental to good teaching. This paper attempts to conceptualise one perspective of pedagogical artistry, that of teacher dialogic artistry. This conceptualisation is built on two dimensions of teachers' conduct aesthetically embodied in dialogic pedagogy: the pedagogical dispositions and language qualities. In this light, we suggest three dispositions that teachers need to develop a dialogic ecology in their class. These are togetherness, provisionality and exploratory disposition. It is also essential that each of these dispositions be accompanied by a teacher's code of verbal communication thoroughly harmonised with them. In the context of such dialogic ecology, students are offered the potential to shape their dialogic ethos.